Assessment and treatment of response to name for children with autism spectrum disorder: Toward an efficient intervention model. Issue 4 (23rd June 2020) - Conine, Daniel E.; Vollmer, Timothy R.; Barlow, Molly A.; Grauerholz‐Fisher, Emma; Dela Rosa, Cynthia M.; Petronelli, Abigail K.
Abstract : Response to name (RTN) is an early developmental milestone, deficits in which are associated with autism spectrum disorder (ASD). This study extends previous research by evaluating an assessment and treatment model for RTN with 13 children with ASD. For all participants, phase 1 was a naturalistic social baseline. The 9 children who did not meet mastery criteria in phase 1 underwent a series of treatment conditions in phase 2. In phase 3, treatment components were removed, and generalization was assessed. Results indicated that tangible reinforcement procedures can produce rapid increases in discriminated RTN, sometimes without prompts. The total number of trials to mastery were reduced in the current study relative to previous research. Results also provide preliminary evidence to suggest that the phase 1 baseline condition may produce distinct patterns of RTN that could be used to predict treatment effects and further reduce trials to mastery in future work.